Nomogram of fetal right portal vein diameter at gestational age 30 to 35 weeks and prediction of small for gestational age at birth. Issue 9 (14th June 2021) - Jokkaew, Neranute; Pleankong, Monyada; Smanchat, Buppa; Prommas, Sinart; Bhamarapravatana, Kornkarn; Suwannarurk, Komsun
Abstract: Aim: To construct the nomogram of fetal right portal vein (RPV) diameter at 30 to 35 weeks' gestation in Thai pregnant population and the use of RPV measurement to predicting small for gestational age (SGA) fetus. Methods: A prospective, cross‐sectional study of singleton pregnancies at antenatal visit between 30 and 35 +6 weeks of gestation in single center, Bhumibol Adulyadej Hospital (BAH) was conducted from January to August 2020. Ultrasonography of fetal biometry and RPV diameter measurement were performed as well as immediate newborn birth weight measurement. The nomogram of fetal RPV was developed for standardization for Thai people. Results: A total of 219 singleton pregnant women were enrolled and ultrasonographic measurement of RPV and fetal biometry was obtained. Mean maternal age and gestational period were 29.4 years and 33.0 weeks, respectively. One third of participants were classified as obese. RPV diameter ranged from 1.85 to 6.07 mm and increased linearly with gestational age. The optimal threshold of RPV diameter for diagnosis SGA was less than 3.06 mm with area under ROC curve at a level of 0.613 (95%CI 0.496 to 0.731). Sensitivity and specificity were 38.46% and 83.94%, respectively. There was no fetal death or neonatal morbidity in the present study. Conclusion: RPV diameter increases in size depending on gestational age. RPV diameter at 30 to 35 +6 weeks gestation was a useful measurement for SGA prediction. RPV measurements greater than 3.06 mm strongly indicated normal fetal growth.